Development Model of Gamal (Gliricidia sepium) Biomass-Based Agroindustry as a Renewable Energy Source within Sustainable Agroforestry Systems - Gunawan; Zainuri; Husnul Jannah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Biomass-based renewable energy development is a strategic solution to address the energy crisis and environmental degradation. The gamal plant (Gliricidia sepium) has high potential as a biomass source due to its rapid growth, adaptability to marginal land, and role in increasing soil fertility in agroforestry systems. This study aims to formulate a model for developing a gamal biomass-based agroindustry as a renewable energy source within a sustainable agroforestry framework. The method used is a literature study with a critical analysis and synthesis approach to various relevant studies. The results of the study indicate that gamal biomass has high energy conversion potential through technologies such as biopellets and biogas that are efficient and applicable. This is evident from the analysis of the review results conducted on 15 articles that have gone through a screening process to be used as scientific literature material in this study. Integration of gamal biomass into agro-industrial systems can create economic added value, improve local energy security, and support environmental sustainability by reducing carbon emissions. The novelty of this study lies in the development of a conceptual model that integrates biomass production, energy conversion technology, and sustainability dimensions in a single agroforestry-based agro-industrial system. These findings provide a strategic contribution to the development of locally resource-based renewable energy and strengthening the rural economy.